ASSESSING AND MODELLING DIGITAL RISKS IN PHARMACEUTICAL INDUSTRY - Sanika Gokhale, Pramod Damle, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Companies across all sectors, including Pharmaceutical, are progressively making a shift to a more technology-based work. Work from Home had challenges but the businesses have been able to cope with this shift, with some companies like TCS claiming that by 2025, 75% of the workforce would be working from home. While businesses are adapting to this new work style, the need for managing risk that is associated with it is also growing. Digital and technology transformation have various risks attached to it and managing them is crucial. Digital risk is any risk that is caused when a business goes Digital. Each industry faces potential risks and identifying these risks and working towards securing it, is important. Businesses can face data loss, theft of critical data, privacy breaches due to digital shifts in the business. Businesses can face risks related to automation of businesses, and compliance. This study focuses on a detailed qualitative analysis of perspectives and experiences of the subject matter experts working in the pharmaceutical industry and coding the data to generate detailed inferences and conclusions from the codes